Limited efficacy of somatic cell lysis buffer to purify laboratory mouse sperm. (June 2018) - Pearson, Brandon L; Posselt, Leonie P; Henzel, Kristin S; Ehninger, Dan
Aim: Epigenetic analyses of sperm require pure samples devoid of diploid cell contamination. We sought to determine the efficacy of somatic cell lysis buffer (SCLB) treatment to purify mouse epididymis sperm samples.Materials & methods: Sperm cell concentration, sperm purity, small RNA contents and sperm and somatic marker gene expression was compared in SCLB-treated sperm samples and two different control conditions.Results: The SCLB condition as well as the control condition mimicking the additional pelleting and re-suspension steps resulted in substantial cell loss without evidence of enhanced purification of sperm cells as compared with epididymis-derived sperm samples that were not manipulated further.Conclusion: Molecular analyses focused on sperm cells require high levels of purity in order to avoid high-confounding RNA and cytosolic contributions of nonsperm cells. Our findings advocate gradient or cell sorting-based purification approaches where pure samples are required for sensitive molecular assays.